Development of Learning Media In The Form of Smartphone Applications For Students of Class XI High School on Respiratory System Materials - Rafeah Husni (Bioedunis Journal, 2023)
This study aims to develop learning media, determine the level of appropriateness of the media, and determine the level of effectiveness of learning media in the form of smartphone applications on the respiratory system material on students' mastery of concepts. This type of research is RnD (Research and Development) research with the Borg and Gall development model consisting of 10 steps, namely; 1) research and gathering information about constraints and needs in learning biology through questionnaires and teacher interviews; 2) media development planning based on preliminary research analysis supported by literature review; 3) media development using Unity software based on flowcharts, then validated by a team of experts and revised; 4) media testing on nine students and one teacher; 5) revised revisions based on suggestions; 6) limited field trials by 40 students and 4 teachers; 7) revisions based on suggestions; 8) large group test by 109 students; 9) revision based on suggestions. The research subjects were students and biology teachers at SMA Negeri 1 Panyabungan Selatan, SMA Negeri 3 Panyabungan, and SMA IT Alhusnayain. The data obtained are descriptive data (questionnaire and interview), qualitative data (Likert scale questionnaire), and quantitative data (multiple choice questions). The results showed that 98.2% of students stated that they needed learning media based on smartphone applications. The developed learning media was suitable for use as learning media for class XI high school students based on aspects of display quality, presentation of material benefits in supporting the learning process, use and ease of operationThis study aims to develop learning media, determine the level of appropriateness of the media, and determine the level of effectiveness of learning media in the form of smartphone applications on the respiratory system material on students' mastery of concepts. This type of research is RnD (Research and Development) research with the Borg and Gall development model consisting of 10 steps, namely; 1) research and gathering information about constraints and needs in learning biology through questionnaires and teacher interviews; 2) media development planning based on preliminary research analysis supported by literature review; 3) media development using Unity software based on flowcharts, then validated by a team of experts and revised; 4) media testing on nine students and one teacher; 5) revised revisions based on suggestions; 6) limited field trials by 40 students and 4 teachers; 7) revisions based on suggestions; 8) large group test by 109 students; 9) revision based on suggestions. The research subjects were students and biology teachers at SMA Negeri 1 Panyabungan Selatan, SMA Negeri 3 Panyabungan, and SMA IT Alhusnayain. The data obtained are descriptive data (questionnaire and interview), qualitative data (Likert scale questionnaire), and quantitative data (multiple choice questions). The results showed that 98.2% of students stated that they needed learning media based on smartphone applications. The developed learning media was suitable for use as learning media for class XI high school students based on aspects of display quality, presentation of material benefits in supporting the learning process, use and ease of operation.